Proteasome mapping reveals sexual dimorphism in tissue‐specific sensitivity to protein aggregations. (23rd February 2020) - Jenkins, Edmund Charles; Shah, Nagma; Gomez, Maria; Casalena, Gabriella; Zhao, Dazhi; Kenny, Timothy C; Guariglia, Sara Rose; Manfredi, Giovanni; Germain, Doris
Abstract: Defects in the proteasome can result in pathological proteinopathies. However, the pathogenic role of sex‐ and tissue‐specific sensitivity to proteotoxic stress remains elusive. Here, we map the proteasome activity across nine tissues, in male and female mice, and demonstrate strong sexual dimorphism in proteasome activity, where females have significantly higher activity in several tissues. Further, we report drastic differences in proteasome activity among tissues, independently of proteasome concentration, which are exacerbated under stress conditions. Sexual dimorphism in proteasome activity is confirmed in a SOD1 ALS mouse model, in which the spinal cord, a tissue with comparatively low proteasome activity, is severely affected. Our results offer mechanistic insight into tissue‐specific sensitivities to proteostasis stress and into sex differences in the progression of neurodegenerative proteinopathies. Synopsis: Proteasome activity mapping across nine tissues in female and male mice reveals sex‐ and tissue‐specfic differences in proteostasis capacity and susceptibility to protein aggregation. Proteasome activity displays a strong sexual dimorphism, where females have significantly higher activity in several tissues. Proteasome activity differs drastically between different tissues. The sexual dimorphism in proteasome activity was confirmed in a SOD1 ALS mouse model and shown to be exacerbated by stress. Abstract : Proteasome activity mapping across nine tissues in female and male mice reveals sex‐ and tissue‐specfic differences in proteostasis capacity and susceptibility to protein aggregation.